Technical fitness of leading Russian and foreign female Nordic combined skiers - Belyova, A. N.; Popova, A. I.; Ardashev, A. E. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to make a technical fitness analysis of the national versus foreign women`s Nordic combined sport leaders.